The Role of the Crosstalk Between Gut Microbiota and Immune Cells in the Pathogenesis and Treatment of Multiple Myeloma - Jasiński, Marcin; Biliński, Jarosław; Basak, Grzegorz W. (Frontiers in Immunology, 2022)
Around 10% of all hematologic malignancies are classified as multiple myeloma (MM), the second most common malignancy within that group. Although massive progress in developing of new drugs against MM has been made in recent years, MM is still an incurable disease, and every patient eventually has relapse refractory to any known treatment. That is why further and non-conventional research elucidating the role of new factors in MM pathogenesis is needed, facilitating discoveries of the new drugs. One of these factors is the gut microbiota, whose role in health and disease is still being explored. This review presents the continuous changes in the gut microbiota composition during our whole life with a particular focus on its impact on our immune system. Additionally, it mainly focuses on the chronic antigenic stimulation of B-cells as the leading mechanism responsible for MM promotion. The sophisticated interactions between microorganisms colonizing our gut, immune cells (dendritic cells, macrophages, neutrophils, T/B cells, plasma cells), and intestinal epithelial cells will be shown. That article summarizes the current knowledge about the initiation of MM cells, emphasizing the role of microorganisms in that process.